Persistent viruses in mosquito cultured cell line suppress multiplication of flaviviruses. Issue 8 (August 2018) - Fujita, Ryosuke; Kato, Fumihiro; Kobayashi, Daisuke; Murota, Katsunori; Takasaki, Tomohiko; Tajima, Shigeru; Lim, Chang-Kweng; Saijo, Masayuki; Isawa, Haruhiko; Sawabe, Kyoko
Abstract: In the growth kinetics analysis of flaviviruses in Aedes albopictus C6/36 cell lines obtained from the Japanese Collection of Research Bioresources (JCRB) Cell Bank and the European Collection of Authenticated Cell Culture (ECACC), these two cells line showed different viral susceptibility for Zika virus (ZIKV), Dengue virus (DENV), and Japanese encephalitis virus (JEV). Next-generation sequencing (NGS) analysis revealed that the C6/36 JCRB strain was persistently infected with two viruses without showing any cytopathic effects. The complete sequence analysis demonstrated that the one virus was Menghai rhabdovirus (MERV), which has been found from Aedes albopictus mosquito. The other virus was a novel virus, designated as Shinobi tetravirus (SHTV). Interestingly, the viral susceptibility of these two strains was almost even for Sindbis virus and Getah virus. We cloned SHTV and MERV from JCRB C6/36 cell line and then re-infected them into another C6/36 cell line, resulting in the reproduction of persistent infection with each virus. ZIKV growth was suppressed in SHTV and/or MERV re-infected C6/36 cells also. To our knowledge, this is the first demonstration that persistent infection with rhabdovirus and/or permutotetravirus suppressed flavivirus replication in mosquito cells.